Timetracker capabilities in student project activities - Sorokina, Olga A. (2020)
The purpose of the work is to consider the possibilities of time trackers in the design activities of students. The article presents an analysis of modern time trackers that contribute to the self-organization of students to achieve educational goals. In the context of an increase in the share of independent training in universities and the expansion of distance learning, there is a need for students to master time management, which allows them to conduct activities most productively. Time management involves the use of electronic tools that promote the development of the discipline, self-organization and student planning for the rapid achievement of goals. The article discusses both trackers for large-scale professional activities, control and accounting of working hours, as well as simpler versions of trackers suitable for personal use by students. Time management ensures timely implementation of the project, allows you to evaluate the contribution of each student to the work, and adjust the activities of students. The use of time trackers in performing various tasks, including the implementation of projects, contributes to high-quality visualization of the number of hours spent on the task and, as a result, the development of discipline and self-organization of students.